Bilingualism Narrows Socioeconomic Disparities in Executive Functions and Self‐Regulatory Behaviors During Early Childhood: Evidence From the Early Childhood Longitudinal Study. Issue 4 (10th January 2018) - Hartanto, Andree; Toh, Wei X.; Yang, Hwajin
Abstract : Socioeconomic status (SES) and bilingualism have been shown to influence executive functioning during early childhood. Less is known, however, about how the two factors interact within an individual. By analyzing a nationally representative sample of approximately 18, 200 children who were tracked from ages 5 to 7 across four waves, both higher SES and bilingualism were found to account for greater performance on the inhibition and shifting aspects of executive functions (EF) and self‐regulatory behaviors in classroom. However, only SES reliably predicted verbal working memory. Furthermore, bilingualism moderated the effects of SES by ameliorating the detrimental consequences of low‐SES on EF and self‐regulatory behaviors. These findings underscore bilingualism's power to enrich executive functioning and self‐regulatory behaviors, especially among underprivileged children.